A study on factors which influence family social control at Taman Tasik Utama, Ayer Keroh, Melaka / Nor Azleen Haron and Mahmudah Noor Zubairi - Haron, Nor Azleen; Noor Zubairi, Mahmudah (Faculty of Administrative Science and Policy Studies, 2014)
The issues regarding youth and young generation is becoming the topic of interest which being discussed by many layers of society including the parents. The researchers intend to study the factors contribute to the family social control as the family especially parents play great role in shaping the children development. The purpose of this research is to identify the factors that contributes to the family social control towards children, to examine the significant relationship between factor (parenting style, religious practice and family relationship) with family social control towards children and to examine which factors (parenting style, religious practice or family relationship) are the most influential on the family social control towards children. A convenience sampling was distributed among 152 respondents at Taman Tasik Utama, Ayer Keroh, Melaka and the target group is the parents. From the findings, the factors contribute to family social control was examined. On behalf of parents, the parents agree that all the variables which are the parenting style, religious practices and family relationship has relationship with the control of parents towards their children. And they agree that the family relationship has the greatest influence on their social control towards their children, followed by religious practice and parenting style accordingly. However, this study does not provide strong evidence of the efficacy and accuracy of the results due to some limitations. Hence, some recommendations were highlighted for the future research to be made regarding research of factors contribute to family social control.